2017
DOI: 10.1108/ilt-03-2016-0071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gas slip on the behavior of the aerostatic guideway

Abstract: Purpose This paper aims to better understand the dynamic characteristics of an aerostatic slider caused by a gas film, and the impact of a gas film slip on the load capacity, stiffness and dynamic stiffness of the guideway is studied. Design/methodology/approach In theory, the Navier velocity slip model is introduced for fluid continuous flow equation to calculate the flow state in the micro-state; in experimental techniques, the stiffness experiment of the guideway by digital inductance meter is performed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Chen, D. J. introduced the Navier velocity slip model to improve the theoretical model of the aerostatic guideways. It was found that the first-order velocity slip model was more suitable to predict the performance of aerostatic guideways [21,22]. All the above results show that it is necessary to consider the velocity slip effect in the design of ATBs.…”
Section: Velocity Slip Effectmentioning
confidence: 85%
“…Chen, D. J. introduced the Navier velocity slip model to improve the theoretical model of the aerostatic guideways. It was found that the first-order velocity slip model was more suitable to predict the performance of aerostatic guideways [21,22]. All the above results show that it is necessary to consider the velocity slip effect in the design of ATBs.…”
Section: Velocity Slip Effectmentioning
confidence: 85%
“…Since the air film model contains squirt flow and shear flow, and the Reynolds number Re is small, based on the Wilcox k-ω model, 28 the specific dissipation rate ω is introduced to establish a standard k-ω model. The turbulent kinetic energy k and ω are obtained from the following transport equation ( 5) and (6).…”
Section: Aerostatic Thrust Bearing Modelmentioning
confidence: 99%
“…How to improve their performance has become the focus of many scholars at home and abroad. 3 Chen et al [4][5][6][7][8] studied the coupling effects of velocity slip, rarefaction effect and effective viscosity of the air film on the performance of aerostatic guideway in micro-scale, compared the load capacity and stiffness under different working conditions. Chen et al 9,10 studied the effect of backflow phenomenon and geometric parameters of rectangular grooves on the static performance of aerostatic bearing and made recommendations for bearing design.…”
Section: Introductionmentioning
confidence: 99%
“…The design and manufacture of highprecision aerostatic guideway made of glass material (Lai et al 2019), metal material (Chen et al 2018a), marble material (Yao et al 2016) can achieve the guideway precision with linearity better than 0.1 μ m through the coupling of linear motor and different types of guideways. In addition to the guide rail material, the guide rail media affects the linear accuracy and rigidity, such as gas (Chen et al 2017), liquid (Liu et al 2019), and other factors, among which the aerostatic guide rail has high accuracy and rigidity and the relative aerostatic guide rail has low accuracy and high rigidity. In the precision machining equipment and process design, the machining object and material removal rate are the main parameters to be considered, as well as the electromagnetic characteristics of the motor itself (Gannel 2019).…”
Section: Influence Of Electro-magnetic-mechanical Coupling On Precisimentioning
confidence: 99%